Comparing cognitive emotion regulation strategies between boys with learning disorder and normal boys - Atefeh Zabihi; Nages Hosein zadeh Bahreini; Fatemeh Hosein zadeh Bahreini (مجله علوم روانشناختی, 2018)
Research show that learning disorder is very common in primary school pupils. Moreover, the use of incompatible cognitive emotion regulation strategies is comorbid with other disorders in all age groups. The purpose of the present study is to compare cognitive emotion regulation strategies in children with learning disorder and normal children. This study is categorized as a descriptive study and of casual-comparative type. 50 primary school students in two groups with and without learning disorder were selected using availability sampling method. To collect data (information), the emotion regulation strategies questionnaire - student version- (Garnefski, 2001) with nine subscales was given to 25 students with learning disorder which were studying in specific primary school and 25 normal pupils. The questionnaire assessed in this study was proved to be valid and reliable.